Time perception without metaphors, or down the stream of consciousness without a saddle - Phillips, I (Elsevier, 2014)
To a remarkable extent philosophical (and indeed psychological) analyses of temporal experience are steeped in metaphor. Snapshot theorists declare that experience is atomized and fragmentary, packaged into isolated stills or slices, perhaps with motion ‘painted’ onto each static snapshot (Crick & Koch, 2003). Extensionalists deny that experience, so conceived, could embrace temporally extended phenomena, and urge instead that we think of experience in terms of duration-blocks capable themselves of housing dynamic contents (Dainton, 2010). This is in part the legacy of the tradition. James famously popularizes the doctrine of the specious present by declaring that ‘the practically cognized present is no knife-edge, but a saddle-back, with a certain breadth of its own on which we sit perched, and from which we look in two directions into time’ (1890). And Husserl in discussing what he terms ‘the time-constituting flow’ goes so far as to say that it cannot be described other than metaphorically, that ‘we lack names’ (1991). Whilst theorists of time perception have much to learn from the tradition, we must move beyond metaphor. Many of the most common metaphors obscure important differences and impede understanding. I explore some of the driving motivations towards theorizing about time perception with the aim of clarifying what the force of talk of ‘duration blocks’ or ‘the specious present’ really amounts to. In doing so, I suggest that philosophers can resolve apparently intransigent oppositions and engage more fruitfully with empirical work in the area.